Robust pose estimation for non-cooperative space objects based on multichannel matching method - Zhaoxiang Zhang; Yuelei Xu; Jianing Song (Scientific Reports)
Abstract Accurate space object pose estimation is crucial for various space tasks, including 3D reconstruction, satellite navigation, rendezvous and docking maneuvers, and collision avoidance. Many previous studies, however, often presuppose the availability of the space object’s computer-aided design model for keypoint matching and model training. This work proposes a generalized pose estimation pipeline that is independent of 3D models and applicable to both instance- and category-level scenarios. The proposed framework consists of three parts based on deep learning approaches to accurately estimate space objects pose. First, a keypoints extractor is proposed to extract sub-pixel-level keypoints from input images. Then a multichannel matching network with triple loss is designed to obtain the matching pairs of keypoints in the body reference system. Finally, a pose graph optimization algorithm with a dynamic keyframes pool is designed to estimate the target pose and reduce long-term drifting pose errors. A space object dataset including nine different types of non-cooperative targets with 11,565 samples is developed for model training and evaluation. Extensive experimental results indicate that the proposed method demonstrates robust performance across various challenging conditions, including different object types, diverse illumination scenarios, varying rotation rates, and different image resolutions. To verify the demonstrated approach, the model is compared with several state-of-the-art approaches and shows superior estimation results. The mAPE and mMS scores of the proposed approach reach 0.63° and 0.767, respectively.